In-line rheological properties of rubber toughened Wood Polymer Composites. (October 2019) - Mazzanti, V; Malagutti, L; Blanchard, M; Yi, S; Mollica, F
Abstract: Wood Polymer Composites are materials that are more and more used and studied by both academic and industrial research. Although such materials are successfully substituting natural wood in many relevant applications, still some of their drawbacks limit their widespread diffusion. One of these is their brittleness, which can be limited by blending with a toughening agent. In this study we investigated the rheological properties, in terms of the flow curve and the wall slip characteristics, of a toughened Wood Polymer Composite. Testing was performed using an in-line slit rheometer attached directly to a single screw extruder. The material used for the experiments was a blend of polypropylene-based wood polymer composite compound, containing 35 wt.% of wood flour and a suitable thermoplastic elastomer used as a toughening agent. The results showed a shear thinning behaviour and a significant slip velocity of the material that is beneficial during processing.